Fine particle emissions from tropical peat fires decrease rapidly with time since ignition - Roulston,C; Paton-Walsh,C; Smith,TEL; Guerette,E-A; Evers,S; Yule,CM; Rein,G; Van,der Werf GR (Journal of Geophysical Research: Atmospheres, 2018)
Southeast Asia experiences frequent fires in fuel-rich tropical peatlands, leading to extremeepisodes of regional haze with high concentrations of fine particulate matter (PM2.5) impacting humanhealth. In a study published recently, the first field measurements of PM2.5 emission factors for tropical peatfires showed larger emissions than from other fuel types. Here we report even higher PM2.5 emission factors,measured at newly ignited peat fires in Malaysia, suggesting that current estimates of fine particulateemissions from peat fires may be underestimated by a factor of 3 or more. In addition, we use both field andlaboratory measurements of burning peat to provide the first mechanistic explanation for the high variabilityin PM2.5 emission factors, demonstrating that buildup of a surface ash layer causes the emissions of PM2.5 todecrease as the peat fire progresses. This finding implies that peat fires are more hazardous (in terms ofaerosol emissions) when first ignited than when still burning many days later. Varying emission factors forPM2.5 also have implications for our ability to correctly model the climate and air quality impacts downwindof the peat fires. For modelers able to implement a time-varying emission factor, we recommend an emissionfactor for PM2.5 from newly ignited tropical peat fires of 58 g of PM2.5 per kilogram of dry fuel consumed (g/kg), reducing exponentially at a rate of 9%/day. If the age of the fire is unknown or only a single value may beused, we recommend an average value of 24 g/kg.Plain Language Summary This paper provides evidence that peat fire emissions of fineparticulates are much larger than for other fires when the peat is newly ignited but decrease rapidly as thefire progresses. This is important because it means that newly ignited fires are particularly detrimental toambient air quality in impacted regions.